2012
DOI: 10.4236/am.2012.330190
|View full text |Cite
|
Sign up to set email alerts
|

On the Stable Sequential Kuhn-Tucker Theorem and Its Applications

Abstract: The Kuhn-Tucker theorem in nondifferential form is a well-known classical optimality criterion for a convex programming problems which is true for a convex problem in the case when a Kuhn-Tucker vector exists. It is natural to extract two features connected with the classical theorem. The first of them consists in its possible "impracticability" (the Kuhn-Tucker vector does not exist). The second feature is connected with possible "instability" of the classical theorem with respect to the errors in the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Of course, supercomputers should be used to realize this algorithm. As a next step in the development of inverse scattering methods of subsurface diagnostics, we intend to work out yet more effective and stable dual-regularization algorithms based on sequential approach to Kuhn-Tucker theorem [11].…”
Section: Inverse Scattering Problems: Theory and Solutionsmentioning
confidence: 99%
“…Of course, supercomputers should be used to realize this algorithm. As a next step in the development of inverse scattering methods of subsurface diagnostics, we intend to work out yet more effective and stable dual-regularization algorithms based on sequential approach to Kuhn-Tucker theorem [11].…”
Section: Inverse Scattering Problems: Theory and Solutionsmentioning
confidence: 99%
“…To overcome difficulties associated with the instability of classical optimality conditions, an approach relying heavily on regularization theory [2,9] was proposed in [3,4,7,8] for deriving conditions on min imizing sequences that are stable against errors in initial data in the case of convex programming problems in a Hilbert space. It was found that, despite the substantial instability of optimization problems, stable conditions on elements of minimizing sequences can be obtained by combining optimization methods underlying classical optimality conditions and regularization methods based on duality theory [3,4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, despite the substantial instability of optimization problems, stable conditions on elements of minimizing sequences can be obtained by combining optimization methods underlying classical optimality conditions and regularization methods based on duality theory [3,4,10,11]. Following this approach, conditions expressed in terms of minimizing sequences were obtained in [3,4,7,8]. An important feature of these conditions is that they are nondifferential in nature and entirely similar in structure to classical nondifferential optimality conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations